The Influence of Packaging, Branding and Sales Promotion on the Repurchase Intention Teh Botol Sosro at Has Fried Chicken Cikarang Restaurant - Kuwat Riyanto; Astri Kartini (Kusuma Negara Business School, 2021)
Teh Botol sosro, which is produced by PT. Sinar Sosro, is the first packaged ready-to-drink tea brand in Indonesia that has been developed and maintained for decades. The number of competitors makes Sosro bottled tea still exist fighting in the soft drink market. This study aims to analyze the effect of packaging on partial repurchase intention, branding on partial repurchase intention, sales promotion on partial repurchase intention, and packaging, branding and sales promotion on simultaneous repurchase intention. the target population in this study were the visitors of Has Fried Chicken Cikarang Restaurant. While the sample is respondents who buy bottled tea Sosro. Thus, the respondents who will be observed are 110 respondents. quantitative analysis method using multiple linear regression equation analysis, followed by analysis of determination (R square), partial hypothesis testing (t test) and simultaneously (F test) with an alpha of 5 percent (0.05). Before being analyzed further, the data quality test and classical assumption test were first carried out. analysis tool using SPSS version 23.0 for windows. The results showed that packaging had an effect on partial repurchase intention, branding had an effect on partial repurchase intention, sales promotion had an effect on partial repurchase intention, and packaging, branding, sales promotion had an effect on simultaneous repurchase intention in bottled tea products. sosro at Has Fried Chicken Cikarang.